18F‐fluorodeoxyglucose‐positron emission tomography Findings in Patients with Genetic Frontotemporal Dementia. (20th December 2022) - Yadollahikhales, Golnaz; Mundada, Nidhi S.; Chapleau, Marianne; Rosen, Howard J.; Boxer, Adam L.; Yokoyama, Jennifer S.; Miller, Bruce L.; Gorno‐Tempini, Marilu; Lee, Suzee E.; Seeley, William W.; Hall, Matthew; La Joie, Renaud; et al.
Abstract: Background: Mutations in microtubule‐associated protein tau ( MAPT ), granulin ( GRN ), and hexanucleotide expansion repeat in the open reading frame of chromosome 9 ( C9orf72 ) are found in 60% of familial frontotemporal dementia (FTD) cases. The current study aims to delineate brain regions with reduced glucose metabolism in patients with genetic FTD in comparison with cognitively normal controls. Methods: (18)F‐ fluorodeoxyglucose (FDG)‐positron emission tomography (PET) images were retrospectively obtained from 17 genetic FTD patients. All patients were symptomatic at the time of imaging, and the autopsy was available for 13. Pittsburgh compound B (PiB) amyloid PET scans were done for 13 patients (Table 1). FDG‐PET was collected at Lawrence Berkeley National Laboratory on a PET or PET‐CT scanner as six 5‐min frames acquired 30 min post tracer injection. Standard Uptake Value Ratio (SUVR) images were created for each patient using pons as a reference region. W‐score (age‐adjusted Z‐score) maps were created for each patient's FDG SUVR using a group of neurologically unimpaired controls (N=74, Mean age 65+ 16, 41 female) as reference. Result: On review of single‐subject w‐maps, all patients with MAPT mutation showed hypometabolism in the anteromedial temporal lobes with 66% showing anterolateral temporal hypometabolism and 33% in the frontal and dorsolateral parietal lobes. Hypometabolism in temporal lobes was seen in all GRN patients and 75% had frontal and parietal hypometabolism in an asymmetric pattern. 80% of the C9orf72 patients had hypometabolism in anteromedial temporal and orbitofrontal regions. 60% showed hypometabolism in dorsolateral prefrontal, medial frontal, and anterolateral temporal lobes. Posterior temporal, posterior cingulate, parietal lobe, cerebellum, insula, thalamus, and caudate were hypometabolic in less than 40% of the C9orf72 patients (Figure 1). On group‐level analysis, compared to controls, patients with C9orf72 showed hypometabolism in the frontotemporal regions, cerebellum and thalamus. Hypometabolism in the frontotemporal and parietal regions was seen with GRN mutation. MAPT mutation carriers showed frontal and anteromedial temporal hypometabolism (Figure 2). Conclusion: Hypometabolism in the posterior regions and cerebellum is more suggestive of C9orf72 repeat expansion. An asymmetric pattern of hypometabolism was seen in all GRN mutation carriers. MAPT mutation resulted in a greater degree of hypometabolism in the anterior medial temporal lobes.